The Hormone Ghrelin Prevents Traumatic Brain Injury Induced Intestinal Dysfunction - Bansal, Vishal (Mary Ann Liebert, Inc., 2010)
Intestinal barrier breakdown following traumatic brain injury (TBI) is characterized by increased intestinal permeability, leading to bacterial translocation, and inflammation. The hormone ghrelin may prevent intestinal injury and have anti-inflammatory properties. We hypothesized that exogenous ghrelin prevents intestinal injury following TBI. A weight-drop model created severe TBI in three groups of anesthetized Balb/c mice. Group TBI: animals underwent TBI only; Group TBI/ghrelin: animals were given 10 μg of ghrelin intraperitoneally prior and 1 h following TBI; Group sham: no TBI or ghrelin injection. Intestinal permeability was measured 6 h following TBI by detecting serum levels of FITC-Dextran after injection into the intact ileum. The terminal ileum was harvested for histology, expression of the tight junction protein MLCK and inflammatory cytokine TNF-α. Permeability increased in the TBI group compared to the sham group (109.7 ± 21.8 μg/mL vs. 32.2 ± 10.1 μg/mL; p < 0.002). Ghrelin prevented TBI-induced permeability (28.3 ± 4.2 μg/mL vs. 109.7 ± 21.8 μg/mL; p < 0.001). The intestines of the TBI group showed blunting and necrosis of villi compared to the sham group, while ghrelin injection preserved intestinal architecture. Intestinal MLCK increased 73% compared to the sham group (p < 0.03). Ghrelin prevented TBI-induced MLCK expression to sham levels. Intestinal TNF-α increased following TBI compared to the sham group (46.2 ± 7.1 pg/mL vs. 24.4 ± 2.2 pg/mL p < 0.001). Ghrelin reduced TNF-α to sham levels (29.2 ± 5.0 pg/mL; p = NS). We therefore conclude that ghrelin prevents TBI-induced injury, as determined by intestinal permeability, histology, and intestinal levels of TNF-α. The mechanism for ghrelin mediating intestinal protection is likely multifactorial, and further studies are needed to delineate these possibilities.